Characterization and genomic function analysis of phenanthrene-degrading bacterium Pseudomonas sp. Lphe-2. Issue 5 (15th April 2020) - Ji, Dan; Mao, Zhen; He, Jian; Peng, Sihan; Wen, Hongyu
Abstract: A stain of Pseudomonas sp. Lphe-2, which could degrade phenanthrene as the main carbon and energy source, was isolated from the aerobic sludge of a coking plant. Then its biodegradation characteristics, whole genome sequence and biodegradation pathway were examined. The Lphe-2 strain exhibited broad-spectrum degradation activities for various polycyclic aromatic hydrocarbons (PAHs), including naphthalene (NAP), phenanthrene (PHE), and pyrene (PYR). Under the optimal conditions, the degradation efficiency of phenanthrene (100 mg/L) is 92.76% on the 7th day, and 2-carboxybenzaldehyde and 1-hydroxy-2-naphthoic acid are the major metabolites found in phenanthrene metabolism. Genomic analysis of Pseudomonas sp. Lphe-2 showed that a total of 3879 genes from the Lphe-2 strain were annotated based on the COG classification, and the genomic information was annotated to 185 metabolic pathways. Based on the intermediate metabolites detected by Gas Chromatography-Mass Spectrometer (GC-MS) and all potential phenanthrene-degrading genes identified by BLAST search, a phenanthrene biodegradation pathway of Lphe-2 strain was proposed. These results suggested that Lphe-2 strain has a good prospect in the bioremediation of PAHs pollution.